A Sequential Bioconversion-Purification Process to Produce High Purity Xylo-Oligosaccharides (Xos) from Nothophagus Pumilio Sawdust Wastes - Vera-Vera, C (Elsevier B.V., 2024)
Xylo-oligosaccharide (XOS) production from lignocellulosic biomass (LCB) is an ongoing technology in which the best raw material, catalyst, and reaction conditions remain unclear. This study proposed a three-step sequential operation to produce prebiotic Xylo-oligosaccharide (XOS) from lignocellulosic biomass (LCB) Nothophagus pumillio sawdust. First, a commercial (Enzeco Xylanase S) and recombinant (GtXyl10A) xylanase were evaluated in XOS production from pre-extracted xylan. Then, the effect of auxiliary enzyme addition (α-glucuronidase) was evaluated in xylan hydrolysis, and finally, XOS were purified by three steps of membrane filtrations: an ultrafiltration (UF) followed by two nanofiltrations (NF). From the above, XOS production yield reach 333 [mgxos∙gxylan−1] of highly purified XOS (95 %) when the process was carried out without auxiliary enzyme addition and 473 [mgxos∙gxylan−1] of 96 % purified XOS when auxiliary enzyme was added, resulting in an improvement of the XOS production yield in 42 %.This shows the feasibility to produce high purity prebiotics from sawdust wastes of the forestry industry. © 2024 Elsevier B.V.